Comparison of four methods of colon cancer cell lysates preparation for ex vivo maturation of dendritic cells - Mohammad Roufarshbaf; Nafiseh Esmaeil; Vajihe Akbari (Wolters Kluwer Medknow Publications, 2022)
Background and purpose: One of the most effective methods for the development of dendritic cell (DC)-based cancer immunotherapy is ex vivo pulsing of DCs with tumor cell lysates (TCLs). However, antitumor immune responses of DCs are significantly influenced by how TCLs were prepared. Here, we compared four strategies of TCL preparation derived from colon cancer cells, HT-29, for ex vivo maturation of DCs. Experimental approach: Peripheral blood monocytes were isolated from healthy volunteers and incubated with granulocyte macrophage colony-stimulating factor and interleukin (IL)-4 to differentiate into DCs in 10 days. Morphological properties, phenotype characteristics (i.e. CD83 and CD86), and cytokine production (i.e. IL-10 and interferon gamma) of DCs loaded with four different TCLs (i.e. freeze-thaw, hypochlorous acid (HOCl), hyperthermia, and UV irradiation) were evaluated. Findings/Results: HOCl preparations led to the generation of DCs with higher surface expression of maturation biomarkers (particularly CD83), while UV preparations resulted in DCs with lower levels of surface biomarkers compared to freeze-thawed preparations. The supernatant of DCs pulsed with HOCl preparation showed significantly higher levels of interferon gamma and lower levels of IL-10 compared with the other groups. Conclusion and implications: Our results suggest that pulsing DCs with HOCl preparation may be superior to other TCLs preparation strategies, possibly due to induction of rapid necrotic cell death.